Normal range of white blood cells and differential count of Sudanese in Khartoum state - Taha, Elmutaz H.; Elshiekh, Mohammed; Alborai, Abdelrahim; Hajo, Elnagi Y.; Hussein, Abdelmohisen; Awad, Kamal M.; Ali, Ibrahim A.; Musa, Omer A. (International Journal of Advances in Medicine, 2018)
Background: The normal physiological range for white blood cells and differential count are essential for diagnosis, treatment, follow up and screening. This study aimed at establishing the reference ranges of WBCs and differential count in Sudanese people. Methods: The present study included 444 healthy adult Sudanese from both sexes with age range of 20 – 60 years. Blood samples were obtained from brachial veins and drawn in EDTA tubes. WBCs and differential count were analyzed using Sysmex KX-21 automated hematology analyzer. Full clinical examination was performed, weight and height were measured, and BMI was calculated. Results: The mean WBC count was 5.1±1.5×103/ µl with a range of 3.6 ×103/µl to 6.6 ×103/µl. The mean WBCs count for males and females were 4.969×103/µl and 5.138×103/µl respectively. Neutrophils count was 2.430×103/µl (47%) and mean for lymphocyte count was 2.116×103/µl (41.1%). Conclusions: WBCs count was directly proportional to BMI. The WBCs count of Sudanese people was lower than that of Caucasians and similar to reports from other African countries.